A COMPARATIVE STUDY BETWEEN STUDENTS’ ABILITY IN READING COMPREHENSION BEFORE AND AFTER USING QUIZIZZ AT ENGLISH STUDY PROGRAM OF ISLAMIC UNIVERSITY OF INDRAGIRI - Emi Ratu Sholeha; Felci Tria Sauhana; Melda Yeni (Program Studi Pendidikan Bahasa Inggris, 2024)
In making observation, the researcher found that many students had problems in learning methods in class and also problems in reading comprehension because of them felt that they did not know what the text was about. In reading ability the students find it difficult to understand the text given during the learning process in the class. In this research, the researcher used the Quizizz application with different features than usual but it is more effective in evaluating students learning in teaching reading in a text. The population of this study was all second semester students, totaling 20 students in English Study Program at Islamic University of Indragiri. To get the research data, the researcher gave a test as an instrument. The result of this study indicate that the average score in before using quizizz was 46 while in after using quizizz was 38. The result of analysis, it showed that the value T-observed 1.23 was lower than T-table was 2.03 and 2.72 in significant 5% and 1%. Based on the result, it was provided that the null hypothesis (H0) was accepted and the alternative hypothesis (Ha) was rejected. Therefore, there was no a significant effect of using quizizz on students’ ability in reading comprehension at English Study Program Islamic University of Indragiri.